Implementasi Model PBL Di Kelas V SDN Teluk Tiram 6 Untuk Meningkatkan Keterampilan Kolaborasi - Linda Rosydah (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor, 2025)
This research used Classroom Action Research which was conducted in 3 meetings. The subjects of this study were class V students of Teluk Tiram 6 State Elementary School, class V, totalling 24 people. Qualitative data collection was obtained through observation of educator activities, learner activities and collaboration. As well as quantitative data includes the classical percentage collaboration obtained from group and individual tests. The results showed that the teacher's activity at meeting I obtained